(untitled) (Indo-MathEdu Intellectuals Journal, 2024)
Teachers have a strategic role as the spearhead of human resource development, so teachers play a role in developing the curriculum. Objectives This research explores the role of teachers in developing an independent curriculum. This research method uses a literature review. The main source of this research data is research articles published through google scholar in the last 10 years. Data collection was carried out using the keywords "role of teachers" and "independent curriculum". Data analysis is carried out qualitatively with the stages of data reduction, data presentation, and conclusion drawing. The results of the study were obtained that the independent curriculum is a response to the improvement of the quality of education in Indonesia, especially during the covid 19 pandemic. The independent curriculum empowers students and develops 21st-century skills and accommodates a diversity of talents and interests, however, its implementation faces challenges such as the transformation of learning outcomes, the limitations of student textbooks, and the lack of variety in more inclusive and relevant learning methods. For this reason, the role of teachers is very necessary in the development of the independent curriculum. The role of teachers in the development of the independent curriculum such as implementers, adapters, developers, and researchers